Molecular Study of Virulence Factors (Cysteine Protease-1 and Amoebapore-C) for Entamoeba histolytica in Babylon Province - Entessar Hatif Abd Al-Kathem Al-Murshidi; Ahmed Khudhair Al-Hamairy; Hadi Meziel Khudhair (Institute of Medico-legal Publications Pvt Ltd, 2021)
A molecular study was conducted for the period from December 2019 to May 2020, which includedexamining (50) positive stool samples by using the direct smear method. that was revealed by the method ofpolymerase chain reaction (PCR) using the gene (18SrRNA), with a percentage of 82%, distributed 87.8%for males and 70.6% for females. Then for determine the virulence factors ( Cysteine proteinase-1) and(Amoebapores-C) by using primers, with (PCR)technique , and then electrophoresis on the agarose gel havebeen done , the results were positive for Cysteine proteinase-1 (APC-1) at a wavelength (212 bp) and theAmoebapore-C (Amo-C) at a wavelength (536 bp). Five random positive samples of the PCR product in thecurrent study were sent to Macrogen in South Korea for the purpose of determining the DNA sequence ofthe amoebapore- C gene present in the Entamoeba histolytica, and it is the first study in Iraq and Babylonprovince that is genetically determined by the NCBI These genotypes of the amoebic holes gene are recordedin the gene bank. The results of the study showed that all the transmitted isolates are identical with NCBIisolates with the USA samples registered with the gene bank with accession number AY956434.2, whichare the isolated samples belonging to the American samples and diagnosed with the number MS30-1043 ofthe USA study by the researcher Bhattacharya et al. (2005) with the current study samples As it was 100%identical. These samples were recorded in the genebank for the first time for this Amoebapore C gene underAccession No. For samples (1, 2, 3, 4, 5) in sequences are MT951203, MT951204, MT951205, MT951206and MT951207, respectively.